Genetic Analysis for Seed Traits in Acacia nilotica (Linn.) Willd. Ex Del Ssp. Indica (Benth.) Brenan (Babul) - Dar, M. Ayoub; Nautiyal, S.; Bakshi, Meena; Mehta, H.; Chaturvedi, O. P.; Tomar, J. M. S. (Indian Forester, 2011)
Genetic parameters for nine pod and seed traits. and per cent germination were worked out in thirty seed sources of Acacia nilotica mostly from the state of Haryana, Himachal Pradesh and Punjab. Values for variability expected genetic gain were calculated for aU individual characters. Seed length, seed width and 100 seed weight exhibited high genetic variabiJity, heritability and genetic gain. Correlation study revealed that pod thickness; pod weight, seed length, seed width, seed thickness and 100 seed weight had significant and positive association with germination percentage. These traits therefore should be given priority for improving germination in Acacia nilotica.